Comparative analysis of crop rotation systems: the impact of ginger (Zingiber officinale) and sponge gourd (Luffa aegyptiaca) residues on growth of Chinese cabbage (Brassica rapa var. chinensis) - Yao, Zhangliang; Miao, Jiashun; Wang, Baojun; Xu, Weidong; Wang, Yeqing; Lu, Qiang; Zhang, Jidong (Frontiers in Plant Science, 2024)
Continuous cropping in green house cultivation often leads to increased pest and disease problems, reducing crop quality and yield. Crop rotation is a common strategy to address these issues, This study compared the growth of Chinese cabbage (Brassica rapa var. chinensis) following rotations with ginger (Zingiber officinale) and sponge gourd (Luffa aegyptiaca). The Chinese cabbage exhibited normal growth following ginger rotation but showed abnormal growth after sponge gourd rotation. The study investigated the underlying causes by analyzing soil physicochemical properties and rhizosphere microbial communities of Chinese cabbage using 16S rRNA and ITS sequencing. The results revealed that soil from ginger-Chinese cabbage rotation had higher levels of soil organic carbon (SOC) and available phosphorus (AP), but lower total nitrogen (TN) and available potassium (AK). Despite similar alpha-diversity for both bacterial and fungal communities, distinct bacterial and fungal community structures between two rotation cropping systems were observed. This suggests that even if the alpha-diversity does not change, the composition of the microbial community can shift in ways that might influence soil health and plant growth. Furthermore, redundancy analysis revealed significant correlation between microbial community structures and soil physicochemical properties of two rotation cropping systems. The SOC and TN were revealed to be the most significant of the investigated soil physicochemical parameters with respect to the variation of both bacterial and fungal assemblages, respectively. The identified biomarkers in bacterial community composition furtherly emphasize the potential for specific microbes to influence crop health positively or negatively. We found that the indicator genera of the bacterial community composition of the ginger-Chinese cabbage rotation system were Amycolatopsis (genus), Pseudonocardiales (order), Pseudonocardiaceae (family), Amycolatopsis mediterranei, which are known as producers of secondary metabolites, such as antibiotics. These findings highlight the importance of crop selection in rotation strategies for optimizing agricultural outcomes.